1887 Wis. Sess. Laws 754, ch. 162, § 3, pt. 36 - (:unkn) unknown (My University, 1887)
Authorized the city to regulate and prohibit the concealed carry of any pistol, slung shot, knuckles, bowie knife, dirk, or any other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED